Inverse Kinematics of a Spatial Mechanism using Multibond Graph - Maini, Aman Kumar; Vaz, Anand (Computer Assisted Methods in Engineering and Science, 2020)
Various methods are available to compute kinematics and dynamics in the case of spatial mechanisms. These methods are cumbersome and laborious for large and multibody spatial mechanisms. The bond graph technique is a powerful alternative tool for modeling. A four-link closed-chain 3R2S (3Revolute 2Spherical) spatial mechanism stands out among the other four-link closed-chain spatial mechanisms due to its ability to be used in a number of applications. The main aim of this paper is to compute the inverse kinematics of the mechanism using the bond graph structure of the system. In this paper, modeling of a four-link closed-chain 3R2S spatial mechanism has been conducted using a multibond graph approach. Inverse kinematics of the spatial mechanism, under various applications, has been directly obtained from the bond graph modeling. MATLAB coding for simulation has been done directly from the multibond graph without explicitly deriving system equations. The simulation results have been analyzed and discussed using various plots.